2014
DOI: 10.1210/jc.2014-2349
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Dysfunction in Offspring of Ovarian-Hyperstimulated Women and Effects of Estradiol and Progesterone: A Retrospective Cohort Study and Proteomics Analysis

Abstract: Children born to ovarian-hyperstimulated women displayed cardiovascular dysfunctions. The underlying mechanisms may involve the effects of supraphysiological estradiol and progesterone levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 33 publications
0
39
0
2
Order By: Relevance
“…In a different study conducted in China, researchers did not observe any differences in systemic blood pressure or carotid IMT [43]. However, they did observe significant differences in FMD, carotid systolic and diastolic diameter, diastolic function parameters, and heart rate.…”
Section: Evidence That Art Can Increase the Risk Of Cardiometabolimentioning
confidence: 97%
See 1 more Smart Citation
“…In a different study conducted in China, researchers did not observe any differences in systemic blood pressure or carotid IMT [43]. However, they did observe significant differences in FMD, carotid systolic and diastolic diameter, diastolic function parameters, and heart rate.…”
Section: Evidence That Art Can Increase the Risk Of Cardiometabolimentioning
confidence: 97%
“…Several studies have reported subclinical but significant cardiovascular changes in ART children (Table 1) [3143]. In some of the first reports, systemic blood pressure levels were higher in IVF and ICSI children by comparison with children that were conceived spontaneously [31,33].…”
Section: Evidence That Art Can Increase the Risk Of Cardiometabolimentioning
confidence: 99%
“…The long term health of their children is well worth studying. Our previous work reported that maternal excessive estrogen exposure before pregnancy might predispose offspring to cardiovascular dysfunction (Xu et al, 2014). Here, we provide evidence that pregestational hyperandrogenism may induce alteration of glucose metabolism in offspring.…”
Section: Discussionmentioning
confidence: 99%
“…The Ingenuity Pathway Analysis (IPA) (Qiagen, Valencia, CA, USA) was used to identify the top biological functions and canonical pathways associated with the differentially expressed mRNAs and miRNAs datasets, as described previously [30]. The Fisher's exact test was used to determine the probability that each biological function or canonical pathway assigned to the dataset is explained by chance alone.…”
Section: Functional Analysis and Paired Mirna-mrna Analysismentioning
confidence: 99%